Urethane resin composition, synthetic leather, and method for producing synthetic leather

A urethane resin composition with a nonionic group and specific powder addresses environmental concerns and processing issues, achieving excellent peel strength and texture for synthetic leather applications.

JP7616425B2Active Publication Date: 2025-01-17DIC CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023564908
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-12-02
Filing Date
2022-11-24
Publication Date
2025-01-17
Estimated Expiration
2042-11-24

AI Technical Summary

Technical Problem

Existing solvent-based urethane resin compositions face challenges with environmental regulations due to the use of DMF, and water-based urethane adhesives struggle with peel strength, texture, and processing issues such as short pot life and rapid crosslinking reactions.

Method used

A urethane resin composition comprising a urethane resin with a nonionic group, water, and a specific powder, with a flow initiation temperature of 100°C or higher and a mass ratio of 50/50 to 80/20, which does not require a crosslinking agent and has a long pot life, providing excellent peel strength and texture.

Benefits of technology

The composition is environmentally friendly, offers excellent peel strength and texture, and has immediate releasability, making it suitable for synthetic leather production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007616425000001
    Figure 0007616425000001
  • Figure 0007616425000002
    Figure 0007616425000002
Patent Text Reader

Abstract

The present invention provides a urethane resin composition which contains a urethane resin (A) having a non-ionic group, water (B), and a powder (C), and which is characterized in that the flow initiation temperature of the urethane resin (A) is 100°C or higher, the mass ratio of the urethane resin (A) and water (B) [(A) / (B)] is 50 / 50 to 80 / 20, and the bulk density of the powder (C) is 400 g / L or less. The present invention also provides a synthetic leather which includes at least a base fabric (i), an adhesive layer (ii), and a skin layer (iii), and which is characterized in that the adhesive layer (ii) is formed from the urethane resin composition. This urethane resin composition can form a coating film having excellent peeling strength and texture.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a urethane resin composition, a synthetic leather, and a method for producing the synthetic leather. [Background technology]

[0002] Conventionally, compositions using polyurethane resins have mainly been used as solvent-based urethane resin compositions for various applications, such as artificial leather, synthetic leather, coating agents, glove coatings and glove membranes, adhesives, etc. Dimethylformamide (DMF) is mainly used in these solvent-based urethane resins, but legal restrictions on DMF are becoming stricter every year due to concerns about its adverse effects on living organisms and the environment, and as a result, there is a demand for environmentally friendly products that use weak solvents, water-based products, and solvent-free products (see, for example, Patent Document 1).

[0003] Among these, water-based urethanes (PUDs), which are urethane resins dispersed in water, are used for the above-mentioned applications. One-component adhesives that use only PUD base resins do not require aging, but it is difficult to control the amount of adhesive soaked in, and there are issues with texture and peel strength, making them difficult to use in practice.

[0004] On the other hand, two-component adhesives that combine a PUD base agent and an isocyanate crosslinking agent have a short pot life, making it difficult to process stably. Also, two-component adhesives that combine a PUD base agent and an oxazoline crosslinking agent have a long pot life, but the strength of the crosslinked film is weak, resulting in low peel strength of the processed product, making them difficult to use in practice. Furthermore, two-component adhesives that combine a PUD base agent and a carbodiimide crosslinking agent have a long pot life and a strong crosslinked film, but the crosslinking reaction is too fast to be processed into an adhesive. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2007-119749 A Summary of the Invention [Problem to be solved by the invention]

[0006] An object of the present invention is to provide a water-containing urethane resin composition that provides excellent peel strength and texture. [Means for solving the problem]

[0007] The present invention provides a urethane resin composition containing a urethane resin (A) having a nonionic group, water (B), and powder (C), wherein the urethane resin (A) has a flow-initiation temperature of 100°C or higher, the mass ratio of the urethane resin (A) to the water (B) [(A) / (B)] is in the range of 50 / 50 to 80 / 20, and the bulk density of the powder (C) is 400 g / L or lower.

[0008] The present invention also provides a synthetic leather having at least a base fabric (i), an adhesive layer (ii), and a skin layer (iii), characterized in that the adhesive layer (ii) is formed from the urethane resin composition.

[0009] The present invention also provides a method for producing an artificial leather, which comprises coating the urethane resin composition and laminating another layer before the composition is completely cured. Effect of the Invention

[0010] The urethane resin composition of the present invention contains water and is environmentally friendly. The urethane resin composition is excellent in peel strength and texture. Furthermore, the urethane resin composition does not require a crosslinking agent, has a long pot life, and is excellent in quick peelability.

[0011] Therefore, the urethane resin composition of the present invention can be suitably used in the production of synthetic leather, and can be suitably used in particular as an adhesive layer for synthetic leather. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The urethane resin composition of the present invention contains a specific urethane resin (A), water (B), and a specific powder (C).

[0013] It is essential that the urethane resin (A) used has a flow initiation temperature of 100° C. or higher. The urethane resin (A) does not thermally melt during drying, suppresses penetration into the base fabric, etc., and provides excellent peel strength and a soft feel. The flow initiation temperature of the urethane resin (A) is preferably 100 to 220° C., more preferably 120 to 200° C., in order to further enhance the above effects.

[0014] The flow-start temperature of the urethane resin (A) can be adjusted by adjusting the type and amount of the chain extender (a1), polyol (a2), and polyisocyanate (a3) ​​used, which are the raw materials of the aqueous urethane resin (A) described later. Examples of the method for adjusting the flow-start temperature to a high level include using a polycarbonate polyol or polyether polyol as the polyol (a2), increasing the amount of the chain extender (a1), and using a polyisocyanate with high crystallinity such as 4,4'-diphenylmethane diisocyanate or dicyclohexylmethane diisocyanate as the polyisocyanate (a3). Examples of the method for adjusting the flow-start temperature to a low level include using a polyester polyol as the polyol (a2), decreasing the amount of the chain extender (a1), and using a polyisocyanate with low crystallinity such as toluene diisocyanate or isophorone diisocyanate as the polyisocyanate (a3). Therefore, by appropriately selecting these methods, it is possible to adjust the flow temperature of the urethane resin (A). The method for measuring the flow temperature of the urethane resin (A) will be described in the examples below.

[0015] The urethane resin (A) has a nonionic group and is dispersible in water. In addition, the urethane resin (A) has a nonionic group, so that when the urethane resin composition of the present invention is used as an adhesive, the adhesive is easily thickened and the tendency to decrease in viscosity during drying is reduced. The adhesive is prevented from penetrating into the base fabric during drying, and excellent peel strength and soft texture can be obtained.

[0016] As a method for obtaining the urethane resin having a nonionic group, for example, a method using a compound having an oxyethylene structure as a raw material can be mentioned.

[0017] As the compound having an oxyethylene structure, for example, polyether polyols having an oxyethylene structure such as polyethylene glycol, polyoxyethylene polyoxypropylene glycol, polyoxyethylene polyoxytetramethylene glycol, and polyethylene glycol dimethyl ether can be used. These compounds may be used alone or in combination of two or more. Among these, it is preferable to use polyethylene glycol and / or polyethylene glycol dimethyl ether, since hydrophilicity can be controlled more easily.

[0018] The number average molecular weight of the compound having an oxyethylene structure is preferably in the range of 200 to 10,000, more preferably in the range of 300 to 3,000, still more preferably in the range of 300 to 2,000, and particularly preferably in the range of 300 to 1,000, in order to obtain even better emulsifiability and water dispersion stability. The number average molecular weight of the compound having an oxyethylene structure is a value measured by gel permeation column chromatography (GPC).

[0019] Specifically, the urethane resin (A) may be, for example, a reaction product of a chain extender (a1), a polyol (a2), a polyisocyanate (a3), and the compound having an oxyethylene structure.

[0020] The chain extender (a1) may have a molecular weight of less than 500 (preferably in the range of 50 to 450). Specifically, the chain extender (a1) may be ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, dipropylene glycol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, hexamethylene glycol, sucrose, methylene glycol, glycerin, sorbitol, bisphenol A, 4,4'-dihydroxydiphenyl, and 4,4'-dihydroxydiphenyl ether. , trimethylolpropane, and other hydroxyl group-containing chain extenders; ethylenediamine, 1,2-propanediamine, 1,6-hexamethylenediamine, piperazine, 2,5-dimethylpiperazine, isophoronediamine, 1,2-cyclohexanediamine, 1,3-cyclohexanediamine, 1,4-cyclohexanediamine, 4,4'-dicyclohexylmethanediamine, 3,3'-dimethyl-4,4'-dicyclohexylmethanediamine, 1,4-cyclohexanediamine, hydrazine, and other amino group-containing chain extenders can be used. These chain extenders may be used alone or in combination of two or more. The molecular weight of the chain extender (a1) is a value calculated from the chemical formula.

[0021] As the chain extender (a1), a chain extender having an amino group (hereinafter abbreviated as "amine-based chain extender") is preferred because it can easily extend the chain even at a relatively low temperature of 30°C or less, and energy consumption during the reaction can be suppressed, and because the introduction of a urea group provides better mechanical strength, film-forming properties, texture, low-temperature bending resistance, quick peelability, and peel strength, and because it makes it easier to achieve high solidification of the urethane resin (A), and it is more preferable to use an amine-based chain extender having a molecular weight in the range of 30 to 250. When two or more types of chain extenders are used in combination, the molecular weight indicates the average value, and it is sufficient that the average value is included in the preferred molecular weight range.

[0022] The proportion of the chain extender (a1) used is more preferably 0.1 to 30 mass %, particularly preferably 0.5 to 10 mass %, of the total mass of the raw materials constituting the urethane resin (A), from the viewpoints of obtaining even better mechanical strength, film-forming properties, texture, peel strength, quick peelability, emulsifiability, low-temperature flexibility, and water dispersion stability, and of facilitating high solids fractionation of the urethane resin (A).

[0023] As the polyol (a2), for example, polyether polyol, polyester polyol, polyacrylic polyol, polycarbonate polyol, polybutadiene polyol, etc. can be used. These polyols may be used alone or in combination of two or more. As the polyol (a2), a compound other than the compound having the oxyethylene structure that imparts the nonionic group is used.

[0024] From the viewpoint of the mechanical strength of the resulting film, the number average molecular weight of the polyol (a2) is preferably in the range of 500 to 100,000, and more preferably in the range of 800 to 10,000. The number average molecular weight of the polyol (a2) is a value measured by gel permeation column chromatography (GPC).

[0025] The proportion of the polyol (a2) used is more preferably in the range of 40 to 90 mass %, particularly preferably 50 to 80 mass %, of the total mass of the raw materials constituting the urethane resin (A), in terms of obtaining even better mechanical strength.

[0026] Examples of the polyisocyanate (a3) ​​include aromatic polyisocyanates such as phenylene diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate, xylylene diisocyanate, naphthalene diisocyanate, polymethylene polyphenyl polyisocyanate, and carbodiimidized diphenylmethane polyisocyanate; and aliphatic or alicyclic polyisocyanates such as hexamethylene diisocyanate, lysine diisocyanate, cyclohexane diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate, xylylene diisocyanate, tetramethylxylylene diisocyanate, dimer acid diisocyanate, and norbornene diisocyanate. These polyisocyanates may be used alone or in combination of two or more.

[0027] The proportion of the polyisocyanate (a3) ​​used is more preferably in the range of 5 to 40 mass %, particularly preferably 10 to 35 mass %, of the total mass of the raw materials constituting the urethane resin (A), in terms of obtaining even better mechanical strength.

[0028] The proportion of the compound having an oxyethylene structure used is preferably 5 mass % or less, more preferably 3 mass % or less, and even more preferably in the range of 0.25 to 3 mass %, based on the total mass of the raw materials constituting the urethane resin (A), in order to obtain even better emulsifiability, water dispersion stability, texture, quick peelability, low-temperature flexibility, and film-forming properties.

[0029] The average particle size of the urethane resin (A) is preferably in the range of 0.01 to 1 μm, more preferably in the range of 0.05 to 0.9 μm, in order to obtain even better texture, low-temperature flexibility, and film-forming properties. The method for measuring the average particle size of the urethane resin (A) will be described in the Examples below.

[0030] In the urethane resin composition of the present invention, the mass ratio [(A) / (B)] of the urethane resin (A) to water (B) must be in the range of 50 / 50 to 80 / 20. Within this range, the adhesive liquid becomes more viscous as it dries before the adhesive liquid becomes less viscous due to a temperature rise during drying. This makes it possible to suppress the adhesive from penetrating into the base fabric, etc., and to obtain excellent peel strength and texture. The mass ratio is more preferably 50 / 50 to 70 / 30.

[0031] The water (B) may be ion-exchanged water, distilled water, etc. These waters may be used alone or in combination of two or more kinds.

[0032] Next, a method for producing the urethane resin (A) used in the present invention will be described.

[0033] The method for producing the urethane resin (A) used in the present invention comprises a step of reacting the polyol (a2), the polyisocyanate (a3), and the compound having an oxyethylene structure in the absence of a solvent to obtain a urethane prepolymer (i) having an isocyanate group (hereinafter abbreviated as the "prepolymer step"); then, dispersing the urethane prepolymer (i) in water (hereinafter abbreviated as the "emulsification step"); and thereafter, reacting with the chain extender (a1) to obtain the urethane resin (A) (hereinafter abbreviated as the "chain extension step").

[0034] The prepolymerization step is preferably carried out without a solvent. In the prior art, the prepolymerization step was generally carried out in an organic solvent such as methyl ethyl ketone or acetone, but a desolvation step for distilling off the organic solvent was required after the emulsification step, and this required several days of production at an actual production site. In addition, it is difficult to completely distill off the organic solvent in the desolvation step, and in many cases a small amount of organic solvent remains, making it difficult to fully comply with environmental requirements. On the other hand, by producing a prepolymer without a solvent, a urethane resin that is completely free of organic solvent can be obtained, and the production step can also be made more labor-saving.

[0035] The prepolymer process can be carried out using a reaction vessel equipped with an agitator; a kneader, a continuous kneader, a taper roll, a single-screw extruder, a twin-screw extruder, a triple-screw extruder, a universal mixer, a Plastomill, a Bodeta-type kneader, or other kneading machine; a rotary dispersion mixer such as a TK Homomixer, Filmix, Ebara Milder, Clearmix, Ultra-Turrax, Cavitron, or Biomixer; an ultrasonic dispersion device; or a device that has no moving parts and can mix by the flow of the fluid itself, such as an in-line mixer.

[0036] In the prepolymer step, the molar ratio [isocyanate groups / (hydroxyl groups and amino groups)] of the sum of the hydroxyl groups in the polyol (a2) and the hydroxyl groups and amino groups in the compound having an oxyethylene structure to the isocyanate groups in the polyisocyanate (a3) ​​is preferably in the range of 1.1 to 3, and more preferably in the range of 1.2 to 2, in order to obtain even better low-temperature flexibility, crack resistance, film-forming properties, texture, peel strength, and mechanical strength.

[0037] The reaction in the prepolymer step may be carried out, for example, at 50 to 120° C. for 1 to 10 hours.

[0038] The emulsification step can be carried out by using, for example, a reaction vessel equipped with an agitating blade; a kneading machine such as a kneader, a continuous kneader, a taper roll, a single-screw extruder, a twin-screw extruder, a triple-screw extruder, a universal mixer, a Plastomill, or a Bodeta-type kneader; a rotary dispersion mixer such as a homomixer, a static mixer, FILMICX, an Ebara Milder, a Clearmix, an Ultra-Turrax, a Cavitron, or a Biomixer; an ultrasonic dispersion device; or a device that has no moving parts and can mix by the flow of the fluid itself, such as an in-line mixer.

[0039] The emulsification step is preferably carried out at a temperature at which water does not evaporate, for example, in the range of 10 to 90° C. The emulsification step can be carried out using the same equipment as in the prepolymer step.

[0040] The chain extension step is a step of increasing the molecular weight of the urethane prepolymer (i) by reacting the isocyanate group of the urethane prepolymer (i) with the chain extender (a1) to obtain the urethane resin (A). From the viewpoint of productivity, the chain extension step is preferably performed at a temperature of 50° C. or less.

[0041] In the chain extension step, the molar ratio of the isocyanate groups in the urethane prepolymer (i) to the sum of the hydroxyl groups and amino groups in the chain extender (a1) [(hydroxyl groups and amino groups) / isocyanate groups] is preferably in the range of 0.8 to 1.1, and more preferably in the range of 0.9 to 1, in order to obtain even better low-temperature flexibility, crack resistance, film-forming properties, peel strength, quick peelability, texture, and mechanical strength.

[0042] The chain extension step can be carried out using the same equipment as the prepolymer step.

[0043] It is essential that the powder (C) has a bulk density of 400 g / L or less. By using the specific powder (C), the adhesive thickens and the tendency of viscosity reduction during drying is reduced. Therefore, the adhesive is prevented from penetrating into the base fabric during drying, and excellent peel strength and texture are obtained. The bulk density of the powder (C) is preferably 5 to 400 g / L, more preferably 10 to 360 g / L, in order to further enhance the above effects. The bulk density of the powder (C) is a value obtained by precisely weighing the weight of the powder filled in a container with a known volume and weight.

[0044] Examples of the powder (C) that can be used include silica powder, silicone powder, cellulose powder, urethane resin powder, acrylic resin powder, aluminosilica powder, hectorite powder, bentonite powder, etc. Among these, one or more selected from the group consisting of silica powder, silicone powder, and cellulose powder are preferred in terms of further enhancing the above-mentioned effects.

[0045] The amount of the powder (C) used is preferably 0.1 to 15 parts by mass, and more preferably 0.1 to 10 parts by mass, per 100 parts by mass of the urethane resin (A), in that the above-mentioned effects can be further enhanced.

[0046] The urethane resin composition of the present invention contains the urethane resin (A), water (B), and powder (C) as essential components, and may contain other additives as necessary.

[0047] Examples of the other additives include surfactants, emulsifiers, neutralizers, thickeners, urethanization catalysts, fillers, pigments, dyes, flame retardants, leveling agents, and antiblocking agents. These additives may be used alone or in combination of two or more. It is preferable that the urethane resin (A) is produced without substantially containing an organic solvent, but an organic solvent may be added as an additive.

[0048] As described above, the urethane resin composition of the present invention contains water and is environmentally friendly. The urethane resin composition is also excellent in peel strength and texture. Furthermore, the urethane resin composition does not require a crosslinking agent, has a long pot life, and is also excellent in quick peelability. Therefore, the urethane resin composition of the present invention can be suitably used in the production of synthetic leather, and can be suitably used in particular as an adhesive layer for synthetic leather.

[0049] Next, the synthetic leather in which the urethane resin composition of the present invention is used as the material for the adhesive layer will be described.

[0050] The synthetic leather has at least a base fabric (i), an adhesive layer (ii), and a skin layer (iii), and specifically has, for example, the following configuration. (1) Base fabric (i), adhesive layer (ii), skin layer (iii) (2) Base fabric (i), adhesive layer (ii), intermediate layer, skin layer (iii) (3) Base fabric (i), wet porous layer, adhesive layer (ii), skin layer (iii) (4) Base fabric (i), wet porous layer, adhesive layer (ii), intermediate layer, skin layer (iii)

[0051] Examples of the base fabric (i) that can be used include nonwoven fabrics, woven fabrics, knitted fabrics, and the like made of polyester fibers, polyethylene fibers, nylon fibers, acrylic fibers, polyurethane fibers, acetate fibers, rayon fibers, polylactic acid fibers, cotton, hemp, silk, wool, glass fibers, carbon fibers, and blends thereof.

[0052] The wet porous layer may be formed by a known wet film-forming method using a solvent-based urethane resin composition.

[0053] Materials that can be used to form the intermediate layer and the surface layer (iii) include, for example, known aqueous urethane resins, solvent-based urethane resins, solventless urethane resins, aqueous acrylic resins, silicone resins, polypropylene resins, polyester resins, etc. These resins may be used alone or in combination of two or more kinds.

[0054] The thickness of the adhesive layer (ii) is, for example, in the range of 30 to 60 μm.

[0055] The flow starting temperature of the adhesive layer (ii), i.e., the flow starting temperature of the cured product of the urethane resin composition of the present invention, is preferably 155° C. or higher, and more preferably in the range of 160 to 220° C., in order to obtain even better heat resistance. The method for measuring the flow starting temperature of the cured product of the urethane resin composition will be described in the examples below.

[0056] Next, a method for producing the synthetic leather having the above-mentioned configuration (1) will be described.

[0057] The synthetic leather can be produced, for example, by coating a resin for forming a skin layer on a release-treated substrate, drying and processing the resin to obtain a skin layer (iii), coating the urethane resin composition of the present invention on the skin layer (iii), and laminating the urethane resin composition to the base fabric (i) before the urethane resin composition is completely cured. These methods are called wet lamination or semi-wet lamination. By using such a method, it is possible to obtain a much better peel strength.

[0058] Examples of the method for applying the urethane resin include methods using an applicator, a roll coater, a spray coater, a T-die coater, a knife coater, a comma coater, and the like.

[0059] After the synthetic leather is produced, it may be aged, for example, at 30 to 100° C. for 1 to 10 days, if necessary. EXAMPLES

[0060] The present invention will now be described in more detail with reference to examples.

[0061] [Example 1] In the presence of 0.1 part by mass of stannous octoate, 1,000 parts by mass of polyether polyol ("PTMG2000" manufactured by Mitsubishi Chemical Corporation, number average molecular weight: 2,000, hereafter abbreviated as "PTMG"), 38 parts by mass of polyethylene glycol ("PEG600" manufactured by NOF Corporation, number average molecular weight: 600, hereafter abbreviated as "PEG"), and 262 parts by mass of dicyclohexylmethane diisocyanate (hereafter abbreviated as "HMDI") were reacted at 100°C until the NCO% reached 2.8% by mass, to obtain urethane prepolymer A1. 1,000 parts by mass of the urethane prepolymer A1 heated to 70° C. was mixed with 200 parts by mass of a 20% by mass aqueous solution of sodium dodecylbenzenesulfonate ("Neogen S-20F" manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) and 650 parts by mass of water to obtain an emulsion. Immediately afterwards, an aqueous dilution of piperazine (hereinafter abbreviated as "PP") with an amino group content equivalent to 95% of the NCO groups was added to extend the chain, finally obtaining an aqueous dispersion of urethane resin with a non-volatile content of 50% by mass of the urethane resin. 100 parts by mass of this urethane resin water dispersion, 5 parts by mass of powder ("Acematt OK-412" manufactured by Evonik, silica powder having a bulk density of 130 g / L, hereinafter abbreviated as "OK-412"), and 0.1 parts by mass of an antifoaming agent ("TEGO FOAMEX800" manufactured by Evonik) were placed in a container and stirred at 2,000 rpm for 2 minutes using a mechanical mixer, and then defoamed using a vacuum defoamer to obtain a urethane resin composition (1).

[0062] [Example 2] A urethane resin composition (2) was obtained in the same manner as in Example 1, except that in Example 1, the type of PTMG was changed to a polycarbonate polyol ("ETERNACOLL UH-100" manufactured by Ube Industries, Ltd., number average molecular weight: 1,000) and the mass ratio of the urethane resin to water was changed to 60 / 40.

[0063] [Example 3] A urethane resin composition (3) was obtained in the same manner as in Example 1, except that the type of PTMG in Example 1 was changed to a polyester polyol ("Placcel 210" manufactured by Daicel Corporation, number average molecular weight: 1,000).

[0064] [Example 4] A urethane resin composition (4) was obtained in the same manner as in Example 1, except that the type of OK-412 in Example 1 was changed to cellulose powder ("KC-Flock W-200Y" manufactured by Nippon Paper Chemicals Co., Ltd., bulk density: 350 g / L, hereinafter abbreviated as "W-200Y").

[0065] [Comparative Example 1] A urethane resin composition (R1) was obtained in the same manner as in Example 1, except that the type of OK-412 in Example 1 was changed to a silicone resin powder ("KMP-590" manufactured by Shin-Etsu Chemical Co., Ltd., bulk density: 580 g / L, hereinafter abbreviated as "KMP-590").

[0066] [Comparative Example 2] An aqueous resin composition (R2) containing an aqueous dispersion of urethane resin (1) was obtained in the same manner as in Example 1, except that the type of OK-412 in Example 1 was changed to a urethane resin powder ("Art Pearl JMB-800" manufactured by Negami Chemical Industrial Co., Ltd., bulk density: 413 g / L, hereinafter abbreviated as "JMB-800").

[0067] [Comparative Example 3] A urethane resin composition (R3) was obtained in the same manner as in Example 1, except that OK-412 was not used.

[0068] [Comparative Example 4] In the presence of 0.1 parts by mass of stannous octylate, 1,000 parts by mass of polyether polyol ("PTMG1000" manufactured by Mitsubishi Chemical Corporation, number average molecular weight: 1,000) and 444 parts by mass of isophorone diisocyanate were reacted at 70°C until the NCO% reached 2.9%, and then 619 parts by mass of acetone was added to obtain an acetone solution of urethane resin. 365 parts by mass of a 50% aqueous solution of sodium diaminoethylsulfone and 1639 parts by mass of ion-exchanged water were mixed with this urethane resin solution to effect phase inversion emulsification, thereby obtaining an emulsion in which the urethane resin was dispersed in water. Next, acetone was distilled off from the emulsion to obtain an aqueous urethane resin dispersion having a non-volatile content of 50% by mass. The flow initiation temperature of the urethane resin was 180°C. 100 parts by mass of this urethane resin water dispersion, 5 parts by mass of OK-412, and 0.1 parts by mass of an antifoaming agent (TEGO FOAMEX800 manufactured by Evonik) were placed in a container and stirred at 2,000 rpm for 2 minutes using a mechanical mixer, and then defoamed using a vacuum defoamer to obtain a urethane resin composition (R4).

[0069] [Comparative Example 5] In the presence of 1,225 parts by mass of methyl ethyl ketone and 0.1 parts by mass of stannous octylate, 1,000 parts by mass of polyether polyol ("PTMG1000" manufactured by Mitsubishi Chemical Corporation, number average molecular weight: 1,000), 50 parts by mass of 2,2'-dimethylolpropionic acid, and 175 parts by mass of isophorone diisocyanate were reacted at 70°C until the solution viscosity reached 20,000 mPa·s, and then 3 parts by mass of methanol were added to terminate the reaction, obtaining a methyl ethyl ketone solution of anionic urethane resin. After mixing this urethane resin solution with 61 parts by mass of polyoxyethylene distyrenated phenyl ether (Hydrophile-Lipophile Balance; 13) and 38 parts by mass of triethylamine, 2,450 parts by mass of ion-exchanged water was added to perform phase inversion emulsification, obtaining an emulsion in which the urethane resin was dispersed in water. Next, methyl ethyl ketone was distilled off from the emulsion to obtain an aqueous urethane resin dispersion having a non-volatile content of 50% by mass. The flow initiation temperature of the urethane resin was 40° C. or lower. 100 parts by mass of this urethane resin water dispersion, 5 parts by mass of OK-412, and 13 parts by mass of a carbodiimide crosslinking agent ("Carbodilite V-04" (solid content 40% by mass) manufactured by Nisshinbo Chemical Inc.), hereinafter abbreviated as "V-04") were placed in a container and stirred at 2,000 rpm for 2 minutes using a mechanical mixer, and then defoamed using a vacuum defoamer to obtain a urethane resin composition (R5).

[0070] [Comparative Example 6] A urethane resin composition (R6) was obtained in the same manner as in Example 1, except that water was added so that the mass ratio of the urethane resin to the water was adjusted to 40 / 60.

[0071] [Method for measuring number average molecular weight] The number average molecular weights of polyols and the like used in the examples and comparative examples are values ​​measured by gel permeation column chromatography (GPC) under the following conditions.

[0072] Measurement equipment: High-speed GPC equipment (Tosoh Corporation "HLC-8220GPC") Column: The following columns manufactured by Tosoh Corporation were used, connected in series. "TSKgel G5000" (7.8mm I.D. x 30cm) x 1 "TSKgel G4000" (7.8mm I.D. x 30cm) x 1 "TSKgel G3000" (7.8mm I.D. x 30cm) x 1 "TSKgel G2000" (7.8mmI.D. x 30cm) x 1 Detector: RI (differential refractometer) Column temperature: 40℃ Eluent: tetrahydrofuran (THF) Flow rate: 1.0mL / min Injection volume: 100 μL (sample concentration 0.4% by mass in tetrahydrofuran solution) Standard sample: A calibration curve was prepared using the following standard polystyrene.

[0073] (Standard polystyrene) "TSKgel Standard Polystyrene A-500" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene A-1000" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene A-2500" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene A-5000" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-1" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-2" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-4" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-10" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-20" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-40" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-80" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-128" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-288" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-550" manufactured by Tosoh Corporation

[0074] [Method for measuring the flow temperature of urethane resin (A)] The urethane resin aqueous dispersion obtained in each of the Examples and Comparative Examples was applied to release paper (coating thickness: 150 μm), and dried in a hot air dryer at 70° C. for 4 minutes and then at 120° C. for 2 minutes to obtain a dried product. The flow start temperature of this dried product was measured using a flow tester "CFT-500A" manufactured by Shimadzu Corporation (using a die with an aperture of 1 mm and a length of 1 mm, a load of 98 N, and a temperature rise rate of 3° C. / min).

[0075] [Method of preparing epidermal layer compound solution] 100 g of the ether-based PUD "HYDRAN WLS-120AR" (DIC Corporation), 2.0 g of the thickener "Borch Gel ALA" (Borchers), the leveling agent "TEGO Flow425" (Evonik Corporation), the defoamer "TEGO Twin4000" (Evonik Corporation), and the black pigment "DILAC HS-9550" (DIC Corporation) were stirred at 2000 rpm for 2 minutes in a mechanical mixer and then defoamed using a vacuum defoamer to prepare a surface layer formulation liquid.

[0076] [How to make synthetic leather] The skin layer compound liquid was coated on release paper EK-100D (manufactured by Lintech) using a knife coater (coating thickness: 100 μm), and then a skin layer film was formed using a hot air dryer (drying conditions: 70° C. for 2 minutes, then 120° C. for 2 minutes). The urethane resin compositions obtained in the Examples and Comparative Examples were further coated on the skin layer film using a knife coater (the coating thickness was adjusted so that the coating thickness would be 50 μm when dried), and a fabric substrate was placed on the urethane resin composition layer (adhesive layer), and the layers were bonded together using a laminator under conditions of a temperature of 25° C., a pressure of 5 MPa, and a feed speed of 0.5 m / min. The adhesive layer was then dried using a hot air dryer (drying conditions: 120° C. for 2 minutes), and immediately thereafter peeled off from the release paper to obtain a processed synthetic leather.

[0077] [Method for measuring peel strength] A 2.5 cm wide hot melt tape ("BW-2" manufactured by Sun Chemical Industry Co., Ltd.) was placed on the surface of the skin layer film of the synthetic leather and heated and pressed at 150°C for 30 seconds to adhere the hot melt tape. A sample was cut along the width of the hot melt tape. A portion of this sample was peeled off, and the substrate and hot melt tape were clamped with a chuck, and the peel strength was measured using a Shimadzu Autograph "AG-1" (manufactured by Shimadzu Corporation) at a full scale of 5 kg and a head speed of 20 mm / min. The average value of the obtained data was calculated and converted to a 1 cm width.

[0078] [Method for evaluating the state of adhesive layer formation] The synthetic leathers obtained in the Examples and Comparative Examples were cut into pieces with a width of 1 mm, and the cross sections of the processed products were observed under an optical microscope and evaluated as follows. "T": An adhesive layer is formed between the skin layer and the substrate "F": No adhesive layer exists between the skin layer and the substrate

[0079] [How to evaluate texture] The synthetic leathers obtained in the Examples and Comparative Examples were evaluated by touch. ◎: Highly flexible, ○: Slightly flexible, △: Poorly flexible, ×: Hard

[0080] [Table 1]

[0081] [Table 2]

[0082] It was found that the urethane resin compositions of the present invention, Examples 1 to 4, were excellent in peel strength and texture.

[0083] On the other hand, in Comparative Examples 1 and 2, which are embodiments in which a powder having a bulk density outside the range specified in the present invention was used as the powder (C), the peel strength and feel were poor.

[0084] Comparative Example 3 is an embodiment in which no powder (C) was used, but the peel strength and feel were poor.

[0085] Comparative Example 4 is an embodiment in which a urethane resin having an anionic group was used instead of the urethane resin (A), but the peel strength and feel were poor.

[0086] Comparative Example 5 is an embodiment in which a urethane resin having an anionic group and a flow starting temperature outside the range specified in the present invention was used instead of the urethane resin (A), but the peel strength and feel were poor.

[0087] In Comparative Example 6, the mass ratio of the urethane resin (A) to the water (B) was outside the range specified in the present invention, and the peel strength and feel were poor.

Claims

1. A urethane resin composition comprising a urethane resin (A) having a nonionic group, water (B), and a powder (C), The urethane resin (A) has a flow initiation temperature of 100° C. or higher, the mass ratio of the urethane resin (A) to the water (B) [(A) / (B)] is in the range of 50 / 50 to 80 / 20; The bulk density of the powder (C) is 400 g / L or less, The urethane resin composition, wherein the powder (C) is at least one selected from the group consisting of silica powder, silicone powder, cellulose powder, urethane resin powder, aluminosilica powder, hectorite powder, and bentonite powder.

2. 2. The urethane resin composition according to claim 1, wherein the nonionic group of the urethane resin (A) is formed by a compound having an oxyethylene structure.

3. 3. A synthetic leather having at least a base fabric (i), an adhesive layer (ii), and a surface layer (iii), wherein the adhesive layer (ii) is formed from the urethane resin composition according to claim 1 or 2.

4. 3. A method for producing an artificial leather, comprising coating the urethane resin composition according to claim 1 or 2, and laminating another layer thereon before the composition is completely cured.

Citation Information

Patent Citations

  • Aqueous polyurethane resin dispersion composition for surface skin layer of fibrous laminate material, method for producing fibrous laminate material and synthetic leather

    JP2007119749A

  • Microporous coating based on polyurethane-polyurea

    JP2009535466A

  • Acid- and alkali-resistant compositions

    JP2022549487A

  • Aqueous resin composition and layered fibrous product

    WO2018100930A1

  • Aqueous dispersion of urethane resin, leather sheet, and method for producing leather sheet

    WO2020174899A1